Assessing Solid Waste Management Practices of Shoreline Cottages in First Class Municipality Public Beach Resorts: A Quantitative Analysis in South Cebu, Philippines - Albiso, Juan; Romaguera, Marjorie; Sardido, Jurisa; Camarillo, Mary Ellen; Alonso Jr., Vevencio; Remolino, Gladys Jane; Gonzales, Liez; Camello, Michael (International Journal of Integrated Engineering, 2025)
Beach resorts are vital to the tourism industry, providing relaxation and recreation for both locals and visitors. However, the enjoyment they offer often comes at a cost to the environment, particularly in the form of solid waste. This study takes a closer look at how shoreline cottages in public beach resorts located in South Cebu, Philippines, manage their waste. Guided by the principles of the Ecological Solid Waste Management Act of 2000, the research assessed current waste generation patterns and evaluated management practices in two first-class municipalities: Argao and Dalaguete. Using a quantitative and descriptive approach, data were gathered from 68 participants, comprising business owners, resort staff, and local government officials, through surveys, interviews, and actual waste sampling. The findings reveal a noticeable difference in the amount of waste produced on busy versus unbusy days, with recyclable materials being the most common type of waste generated. While awareness of proper waste disposal is generally high, issues remain in waste segregation and consistent policy enforcement. Importantly, the study found strong correlations between the local government’s waste management efforts and those of the resorts, particularly in areas like segregation, disposal, and compliance with penalties. The results highlight the need for a more integrated and collaborative approach to waste management—one that strengthens existing practices, improves compliance, and supports sustainable tourism.